2012
DOI: 10.3109/01677063.2011.652266
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Genes Involved in Inflammatory Pathways in Patients with Sudden Sensorineural Hearing Loss

Abstract: Although the etiology of idiopathic sudden sensorineural hearing loss (SSNHL) remains unclear, the pathologically increased permeability of blood vessels, elucidated by gadolinium-enhanced magnetic resonance imaging (MRI), suggests the involvement of inflammation. Because SSNHL is considered a multifactorial disease, possibly caused by interactions between genetic factors and environmental factors, the authors investigated the associations of polymorphisms of inflammatory mediator genes with susceptibility to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 32 publications
2
45
0
2
Order By: Relevance
“…We, therefore, investigated the potential association between IL-6 -572C/G polymorphism and SSNHL. Our results were consistent with a previous study which indicated that IL-6 -572C/G polymorphism might influence the susceptibility to SSNHL in Japanese patients (Hiramatsu et al 2012). The gene encoding ICAM-1 is located on chromosome 19p13.2.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We, therefore, investigated the potential association between IL-6 -572C/G polymorphism and SSNHL. Our results were consistent with a previous study which indicated that IL-6 -572C/G polymorphism might influence the susceptibility to SSNHL in Japanese patients (Hiramatsu et al 2012). The gene encoding ICAM-1 is located on chromosome 19p13.2.…”
Section: Discussionsupporting
confidence: 93%
“…IL-6 promotes atherosclerosis by impairing vascular endothelial cells and contributing to endothelial activation (Papanicolaou et al 1998). Elevated serum concentration of IL-6 has been reported in cardiovascular events and SSNHL (Hou et al 2008;Hiramatsu et al 2012). There is a polymorphism in the promoter region at position -572 of the IL-6 gene, which is C/G.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bazı çalışamalarda, AİK nedeni olarak kronik enfeksiyon üzerinde durulmaktadır (19) . Kronik inflamasyon iskemik hasar oluşturararak mikrovasküler zedelenme ve aterogeneze ortam hazırlar.…”
Section: Bulgularunclassified
“…However, there is no conclusive evidence for any particular hypothesis [2][3][4]. The cause of ISSNHL has been focused on chronic inflammation recently [5]. Chronic inflammation can cause microvascular injury and atherogenesis, which is increasing ischemic risk in a direct manner [6].…”
Section: Introductionmentioning
confidence: 99%